2018
DOI: 10.1177/1477370818764827
|View full text |Cite
|
Sign up to set email alerts
|

The profile and detection of bribery in Norway and England & Wales: A comparative study

Abstract: This paper provides the first significant profile of offenders convicted of bribery in England and Wales (E&W) and Norway, based upon a sample of 75 cases from E&W, and 46 from Norway, which were collected through searches of the media and other relevant sources between 2003 and 2015. The paper provides a profile of bribe payers and takers: illustrating that in both E&W and Norway they are predominantly male and middle aged, involved in a median bribe of between £20k to £30k, with the sector experiencing the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 31 publications
(43 reference statements)
0
5
0
Order By: Relevance
“…However, in other research analysing domestic and international bribery in England and Wales, domestic bribes tend to be 'cheaper' than foreign ones (Andresen & Button, 2018, p. 9). More specifically, 95% of convictions involving bribes under £100,000 were domestic (and 5% were overseas), whereas only 40% of convictions involving bribes over £100,000 were domestic, with 60% overseas (Andresen & Button, 2018). This was later reinforced in interviews with senior CPS staff who alluded to domestic bribery involving relatively small amounts in terms of payments made and a wide geography of cases.…”
Section: The Nature and Scope Of Domestic Briberymentioning
confidence: 99%
“…However, in other research analysing domestic and international bribery in England and Wales, domestic bribes tend to be 'cheaper' than foreign ones (Andresen & Button, 2018, p. 9). More specifically, 95% of convictions involving bribes under £100,000 were domestic (and 5% were overseas), whereas only 40% of convictions involving bribes over £100,000 were domestic, with 60% overseas (Andresen & Button, 2018). This was later reinforced in interviews with senior CPS staff who alluded to domestic bribery involving relatively small amounts in terms of payments made and a wide geography of cases.…”
Section: The Nature and Scope Of Domestic Briberymentioning
confidence: 99%
“…Bussman and Werle [ 24 ] conducted a victimization survey and reported that perpetrators where highly educated, high social status, males over the age of 40. A more recent study conducted in England and Wales and Norway also reports that perpetrators of bribery were male and middle aged [ 25 ]. Similar to this study, Andersen and Button, as well as the ACFE’s Report to the Nation, reinforce that the profiles of white-collar perpetrators are predominately male, middle-aged (approximately 40 years old) and highly educated.…”
Section: Predictors Of Loss Due To Pharmaceutical Fraudmentioning
confidence: 99%
“…We argue that signal intensity for tips to journalists normally is high, as whistleblowers tend to be upset and want to get attention (Andresen & Button, 2019). Furthermore, we suggest that signal alertness is high among journalists, as they are dependent on tips in their daily work to cover news stories.…”
Section: Investigative Journalistsmentioning
confidence: 99%
“…Journalists always need sources to which they have no access unless the sources cooperate with the media. By being polite and receptive, journalists increase the likelihood that whistleblowers and others will contact the media when they learn of potential misconduct and crime (Andresen & Button, 2019). There seems to be a lot to learn from investigative media and their journalists.…”
Section: Investigative Journalistsmentioning
confidence: 99%
See 1 more Smart Citation